A nomogram for predicting the HER2 status of circulating tumor cells and survival analysis in HER2-negative breast cancer - Yang, Yuqin; Li, Liudan; Tian, Wenjing; Qiao, Zhen; Qin, Qi; Su, Liqian; Li, Peiqiu; Chen, Weirong; Zhao, Hong (Frontiers in Oncology, 2022)
Background: In breast cancer patients with HER2-negative tumors (tHER2-), HER2-positive CTCs (cHER2+) were associated with promising efficacy of HER2-targeted therapy, but, controversy has persisted over its prognostic effect. We developed a model including clinicopathologic parameters/blood test variables to predict cHER2 status,and evaluated the prognostic value of cHER2+ in tHER2- patients. Methods: The cHER2+ was detected, and combinded blood test results and clinicopathological characteristics, a nomogram was constructed to predict cHER2 status in tHER2- patients according to logistic regression analysis. The nomogram was evaluated by C-index values and calibration curve. Kaplan–Meier curves, log-rank tests and Cox regression analyses were performed to evaluated the prognostic value of cHER2 status. Results: TNM stage, white blood cells (WBCs), neutrophils (NEUs), uric acid (UA), DeRitis ratio [aspartate transaminase (AST)/alanine transaminase (ALT)] and high-density lipoprotein (HDL) were found to be associated with cHER2 status in tHER2- patients in univariate logistic regression analysis, in which UA and DeRitis ratio remained significant in multivariate logistic regression analysis. A model combining these 6 variables was constructed, the C-index was 0.745(95% CI: 0.630–0.860) and the calibration curve presented a perfect predictive consistency. In survival analysis, patients of the subgroup “with cHER2+/UA-low”(p = 0.015) and “with cHER2+/ DeRitis ratio – high”(p = 0.006) had a significantly decreased disease-free survival (DFS). Conclusions: Our nomogram, based on TNM stage, WBC, NEU, UA, DeRitis ratio and HDL, may excellently predict the cHER2 status of tHER2- patients. Incorporation with UA and De Ritis ratio may enhance the prognostic value of cHER2 status.